Effevtiveness of Regulations for Collecting Income Tax From E-Commerce Transactions Through Social Media Tax Fairness For MSMES - Sumartono Sumartono; Adnan Hamid; Mashlihati Nur Hidayati; Sineenart Suasoongnern (CV. Era Digital Nusantara, 2025)
The information technology revolution has changed the face of global trade, including in Indonesia. Rapid advances in digital technology have had a significant impact on the national trading system, where buying and selling activities are no longer limited to conventional trade but have developed into electronic-based trade transactions. This study analyzes the effectiveness of regulations on the collection of income tax from e-commerce transactions via social media on tax fairness for MSMEs in Indonesia. The evolution of e-commerce tax regulations shows a gradual development from the 2021 HPP Law to PMK 37/2025, but there are still significant legal gaps in the regulation of transactions via social media platforms such as Instagram, Facebook, and WhatsApp Business. Using a normative legal research method with a legislative and conceptual approach, this study applies Soerjono Soekanto’s theory of legal effectiveness and John Rawls’ theory of justice as analytical tools. The findings indicate that PMK 37/2025 is ineffective in reaching social media transactions due to the informal characteristics of these platforms that enable transactions without formal registration, payments through personal transfers, and communication via private chats. This regulatory gap creates distributive injustice that disadvantages traditional MSMEs, who are bound by strict tax obligations while competitors on social media can avoid tax burdens. Soekanto’s theoretical analysis shows the regulation fails to meet the implementability criteria for the social media segment, while Rawls’ theory identifies violations of equality and reasonableness principles that create unfair competition. The study concludes that comprehensive regulation combining technological automation with procedural simplification is necessary to achieve equitable competitive conditions for all business actors.